2022
DOI: 10.1186/s12890-022-01881-8
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse large B-cell lymphoma presenting as reversible intrapulmonary arteriovenous shunts with hypoxia, fever and progressive jaundice: a case report and literature review

Abstract: Background Intrapulmonary arteriovenous shunts is rare seen in a patient without lung involvement. Case presentation This is the first report of reversible intrapulmonary arteriovenous shunts secondary to extrapulmonary lymphoma as one initial symptom. The patient presented as fever of unknown origin and dyspnea, and examinations of infection were negative. Diagnosis of DLBCL was finally confirmed through bone marrow and splenic biopsies. Intrapulm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…In addition, cytolytic activity, DCs, the inflammation-promoting process, neutrophils, and pDCs were clustered into the high-risk group which may provide novel immunotherapy targets which means the hypoxic TME may play a crucial role in pathogeneses and progression in DLBCL. Consistent with previous results, ECM-related features such as basement membrane, integrin binding, and focal adhesion were significantly enriched in the low-risk group based on GO and KEGG pathway analyses, indicating that these factors may be associated with better prognosis (Hou et al, 2022). We further speculated the possible therapeutic targets using the pRRophetic package and found that higher IC50 values of afatinib, bosutinib, ATRA, methotrexate, gemcitabine, veliparib, lenalidomide, GW843682X, etoposide, BI-D1870, and rucaparib, as well as reduced IC50 values of LFM-A13, A-770041, axitinib, lapitinib, imatinib, bryostatin.1, and doramapimod, were observed in the low immune score group which indicated that patients with a higher immune score presented higher sensitivity to afatinib, bosutinib, ATRA, methotrexate, gemcitabine, veliparib, lenalidomide, GW843682X, etoposide, BI-D1870, and rucaparib, as well as lower sensitivity to LFM-A13, A-770041, axitinib, lapitinib, imatinib, bryostatin.1, and doramapimod, and thus show better therapy sensitivity.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition, cytolytic activity, DCs, the inflammation-promoting process, neutrophils, and pDCs were clustered into the high-risk group which may provide novel immunotherapy targets which means the hypoxic TME may play a crucial role in pathogeneses and progression in DLBCL. Consistent with previous results, ECM-related features such as basement membrane, integrin binding, and focal adhesion were significantly enriched in the low-risk group based on GO and KEGG pathway analyses, indicating that these factors may be associated with better prognosis (Hou et al, 2022). We further speculated the possible therapeutic targets using the pRRophetic package and found that higher IC50 values of afatinib, bosutinib, ATRA, methotrexate, gemcitabine, veliparib, lenalidomide, GW843682X, etoposide, BI-D1870, and rucaparib, as well as reduced IC50 values of LFM-A13, A-770041, axitinib, lapitinib, imatinib, bryostatin.1, and doramapimod, were observed in the low immune score group which indicated that patients with a higher immune score presented higher sensitivity to afatinib, bosutinib, ATRA, methotrexate, gemcitabine, veliparib, lenalidomide, GW843682X, etoposide, BI-D1870, and rucaparib, as well as lower sensitivity to LFM-A13, A-770041, axitinib, lapitinib, imatinib, bryostatin.1, and doramapimod, and thus show better therapy sensitivity.…”
Section: Discussionsupporting
confidence: 90%
“…FNDC1, ANTXR1, RARRES2, S100A9, and MT1M were found to be related to prognosis of DLBCL in this study. FNDC1 (fibronectin type III domain containing 1) was found to be related to hypoxia (Zhao et al, 2022) and to be associated with chemoradiation resistance and poor prognosis of gastric cancer, breast cancer, and colorectal cancer by multiple pathways (Ren et al, 2018;Zhong et al, 2018;Liu et al, 2019;Wei et al, 2021;Yunwen et al, 2021;Chen et al, 2022). ANTXR1 is a receptor for anthrax toxin and is highly expressed in tumor endothelial cells.…”
Section: Discussionmentioning
confidence: 99%